Myxoedema coma caused by immunotherapy-related thyroiditis and enteritis. (7th October 2021) - Mc Donald, Darran; Goulden, Eirena; Cullen, Garret; Crown, John; Crowley, Rachel K
Abstract : Summary: Thyroid dysfunction is among the most common immune-related adverse reactions associated with immune checkpoint inhibitors. It most commonly manifests as painless thyroiditis followed by permanent hypothyroidism. This usually causes mild toxicity that does not interfere with oncological treatment. In rare instances, however, a life-threatening form of decompensated hypothyroidism called myxoedema coma may develop. We present a case of myxoedema coma in a woman in her sixties who was treated with a combination of CTLA-4 and PD-1 immune checkpoint inhibitors; for stage four malignant melanoma. She became hypothyroid and required thyroxine replacement after an episode of painless thyroiditis. Six months after the initial diagnosis of malignant melanoma, she presented to the emergency department with abdominal pain, profuse diarrhoea, lethargy and confusion. She was drowsy, hypotensive with a BP of 60/40 mmHg, hyponatraemic and hypoglycaemic. Thyroid function tests (TFTs) indicated profound hypothyroidism with a TSH of 19 mIU/L, and undetectable fT3 and fT4, despite the patient being compliant with thyroxine. She was diagnosed with a myxoedema coma caused by immune-related enteritis and subsequent thyroxine malabsorption. The patient was treated with i.v. triiodothyronine (T3) and methylprednisolone in the ICU. While her clinical status improved with T3 replacement, her enteritis was refractory to steroid therapy. A thyroxine absorption test confirmed persistent malabsorption. Attempts to revert to oral thyroxine were unsuccessful. Unfortunately, the patient's malignant melanoma progressed significantly and she passed away four months later. This is the first reported case of myxoedema coma that resulted from two distinct immune-related adverse reactions, namely painless thyroiditis and enterocolitis. Learning points: Myxoedema coma, a severe form of decompensated hypothyroidism is a rare immunotherapy-related endocrinopathy. Myxedema coma should be treated with either i.v. triiodothyronine (T3) or i.v. thyroxine (T4). Intravenous glucocorticoids should be co-administered with thyroid hormone replacement to avoid precipitating an adrenal crisis. Thyroid function tests (TFTs) should be monitored closely in individuals with hypothyroidism and diarrhoea due to the risk of thyroxine malabsorption. A thyroxine absorption test can be used to confirm thyroxine malabsorption in individuals with persistent hypothyroidism.